2006
DOI: 10.1183/09031936.00058106
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma caused by stainless steel welding fumes: a clinical study

Abstract: The aim of the present study was to describe the cases of occupational asthma (OA) due to stainless steel welding fumes diagnosed at the Finnish Institute of Occupational Health during the period 1994-2003.OA was diagnosed according to patient history, lung function examinations and welding challenge tests with measurements of the forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF) values.The present series comprised 34 patients, all male, with a mean age of 44.7 yrs (range 22-57), mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Despite some improvement in the working conditions and welders' use of respiratory protective equipment, such as motorized respirators, workers are still exposed to fumes produced by co-workers, when they themselves perform tasks other than welding. The pulmonary health effects related to the exposure to welding fumes including chronic bronchitis, pneumonia, metal fume fever, and lung function changes are gene rally well-known [3,5]. However, a growing concern for cardiovascular health effects has emerged, as several studies have reported an increased mortality risk of ischemic heart disease among welders [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite some improvement in the working conditions and welders' use of respiratory protective equipment, such as motorized respirators, workers are still exposed to fumes produced by co-workers, when they themselves perform tasks other than welding. The pulmonary health effects related to the exposure to welding fumes including chronic bronchitis, pneumonia, metal fume fever, and lung function changes are gene rally well-known [3,5]. However, a growing concern for cardiovascular health effects has emerged, as several studies have reported an increased mortality risk of ischemic heart disease among welders [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study on occupational asthma due to welding fumes from stainless steel, it was found that in addition to respiratory symptoms, 21 (62%) patients also had nasal or laryngeal symptoms related to welding fumes [8]. A questionnaire study among 351 welders showed that 40.5% of the respondents had at least one nasal symptom related to welding [1].…”
Section: Introductionmentioning
confidence: 99%
“…The common complaints of the welders were cough, asthma, morning phlegm, fever and lethargy particularly after returning from vacation (12). Hannu et al also reported asthma as the most common complaint in welders (7). According to table 4 forced vital capacity mean, forced expiratory volume in the first second, the ratio of the forced expiratory volume in the first second to the forced vital capacity, maximum expiratory flow, the maximum volume of air per minute, slow vital capacity, current volume, inspiratory and expiratory reserve volume in the welders group were significantly less than those of the control group (P < 0.01).…”
Section: Discussionmentioning
confidence: 97%